Dissemination to State and Private Universities in Indonesia about the Urgency of Developing Communication History Studies - Nisa Alfira; Antoni; Verdy Firmantoro (Civitas Consecratio: Journal of Community Service and Empowerment, 2025)
Communication History falls under Communication Studies, which aims to studyhuman communication practices from a historical perspective. This study isgrowing rapidly in several countries. Simonson et al (2013) wrote The Handbookof Communication History which became one of the main references for studyingCommunication History. In Indonesia, this study is relatively undevelopedby Communication Studies academics. This has become a concern for theDepartment of Communication Science FISIP Universitas Brawijaya (UB) in thelast decade. Several lecturers in the department formed an informal communitycalled Komunitas Pengkaji Komunikasi (KPK). KPK contributes to the developmentof Communication History studies both within UB and nationally. Our communityservice programme this year targets the academic community, namely lecturersand students at various state and private universities in Indonesia. Our teamaims to introduce and invite the Communication Science academic communityto participate in developing the study of Communication History. This goal isachieved through the production of videos containing dialogues that talk aboutwhat is the scope of Communication History studies, the importance of this study,and how the Department of Communication Science FISIP UB contributes to theacademic world by developing Communication History studies.